Coerência e articulação tópica: uma análise a partir de redações do ENEM - Sá, Kleiane Bezerra de (2018)
This paper belongs to the Textual Linguistics area and aims to reshape the defining factors of coherence taking into consideration pragmatic-discursive and semantic aspects from the discursive topic concepts and from the topic articulation strategies by analyzing Enem essays. Starting with discussions around the definition of coherence, reconsidering it in a sociocognitive and discursive dimension, this work establishes connections between the textual aspects of coherence – continuity, progression, articulation and non-contradiction – and the concepts of discursive topic, cohesion and topic articulation mechanisms. Therefore, it is proposed that the analysis of coherence in Enem essays genre should be taken in a broad sense, articulated with the discursive topic and cohesion concepts. Recognizing the relevance of trying to establish theoretical connections between the description of coherence, the cohesion and also the description of the discursive topic, and considering that textual principles cannot be evaluated apart from the genre discursive practices characteristics, 27 essays belonging to the corrector training notebook, from 2013, 2014 and 2015 editions, will be analyzed in order to elaborate a criteria framework in which these analytical parameters can be articulated, combined to Enem’s production and evaluation context. We explore the hypothesis that it is possible and pertinent to relate coherence and cohesion to the topic organization analyses, in order to articulate the evaluation parameters of textual aspects in Enem essays. This evaluative framework of textual aspects proposal can benefit Enem candidates and collaborate to the qualification of teachers who deal with the development of abilities to recognize the construction of ideas in texts and comprehension of articulatory mechanisms that enable the maintenance and progression of topics and subtopics.